Stem cell therapy in improving the motor function of patients with cerebral palsy: Systematic review with meta-analysis (Journal of Rashid Latif Medical College, 2022)
Background: Cerebral palsy (CP) has no cure yet. This study was aimed to evaluate the efficacy and safety of stem cell therapy (SCT) for improving the gross motor function (GMF) of patients with CP.Methods: A systematic literature search was performed in CENTRAL, PubMed, Embase, and Google Scholar to identify relevant randomized controlled trials from the year 2012 to 2022. The outcome measures were GMF and adverse events. For the meta-analysis, treatment effects on GMF improvement were expressed as standardized mean differences (SMD) with 95% confidence intervals (CI), using a random-effects model.Results: There were seven trials that either used autologous or allogenic stem cells, with 411 participants, and were met with inclusion and exclusion criteria. The age, severity, and type of CP in participants varied. Follow up duration ranged from 6 to 24 months. Four studies had single transplantation while the other three had two to four sessions. Overall, a significant positive effect on GMF was seen in SCT than control group, SMD = 2.22 [95% CI 1.15 - 3.29] with a high heterogeneity (I² = 95%). In a separate analysis, umbilical cord blood (UCB) was the most effective cell type, SMD = 3.24 [1.38,5.10]. Serious adverse events were rare, with similar effects in treatment and control groups.Conclusion: A positive and safe effect of SCT, specially UCB on GMF, was observed. However, the standardizations of treatment regimes, therapeutic-cell dose, and SCT optimal timing are needed to maximize the efficacy of treatment.Keywords: Cell Therapy, cerebral palsy, efficacy, motor function, movement disorders, stem cell